1999
DOI: 10.1046/j.1525-1381.1999.99225.x
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Aspects of Expression of Stably Integrated Transgenes in Cells of the Skin In Vitro and In Vivo

Abstract: The observation that transgenes can be stably integrated into the genome of fibroblasts using recombinant retroviruses enhanced interest in using these cells as a vector for gene therapy. This enthusiasm has lessened during the past 8 years, not because skin has lost the features that make it attractive for gene therapy, but rather because stable transgene expression in vivo has not been achieved. All investigators who have used genetically modified fibroblasts to study in vivo aspects of gene therapy have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…Fibroblasts are easy to obtain, cultivate, and store, and the delivery of these robust cells via intradermal injections is practical. In view of regulatory and/or gene therapy vector issues, it would be advantageous that the cells synthesize sufficient amounts of the therapeutic protein yet not require genetic modification, because preliminary studies have shown that genetically modified fibroblasts (29,30) may be effective, but can lose the transgene expression within a relatively short time (38).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts are easy to obtain, cultivate, and store, and the delivery of these robust cells via intradermal injections is practical. In view of regulatory and/or gene therapy vector issues, it would be advantageous that the cells synthesize sufficient amounts of the therapeutic protein yet not require genetic modification, because preliminary studies have shown that genetically modified fibroblasts (29,30) may be effective, but can lose the transgene expression within a relatively short time (38).…”
Section: Discussionmentioning
confidence: 99%
“…55 -59 However, infusion of lymphocytes in patients has been associated with serious side effects, 32,57 and fibroblasts have been reported to be incapable of maintaining long -term survival or expression of exogenous genes in vivo in the absence of a matrix scaffold. 55 The results of the present study demonstrate for the first time that targeted delivery of therapeutic gene -expressing endothelial cells to sites of tumor-associated angiogenesis is a feasible, efficient, safe, and potentially effective strategy to treat established tumor metastases in the lungs.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, stable transgene expression in vivo has not yet been achieved by retrovirus. 38 Plasmid DNA that contains the desired gene can be injected intradermally, and it is rapidly absorbed and expressed by the epidermis. However, gene expression after plasmid injection is only transient.…”
Section: Discussionmentioning
confidence: 99%